Characterization and Usefulness of Clot-Fibrinolysis Waveform Analysis in Critical Care Patients with Enhanced or Suppressed Fibrinolysis - Tsuchida, Takumi; Hayakawa, Mineji; Kumano, Osamu (Thrombosis and Haemostasis, 2023)
Introduction Recently, clot-fibrinolysis waveform analysis (CFWA), which is a coagulation and fibrinolysis global assay based on assessing the activated partial thromboplastin time with tissue-type plasminogen activator, was developed. This study aimed to investigate the characteristics of CFWA using plasma samples from patients in the critical care unit.Materials and Methods The fibrinolysis times using CFWA were measured in 298 plasma samples. These samples were divided into three groups based on the reference interval (RI) of fibrinolysis time using CFWA: shortened group, less than RI; within group, within RI; prolonged group, more than RI. The coagulation and fibrinolysis markers, including D-dimer, plasmin–α2 plasmin inhibitor complex (PIC), fibrin monomer complex (FMC), plasmin–α2 plasmin inhibitor (α2-PI), plasminogen (Plg), and fibrinogen (Fbg) were analyzed and compared among the three groups.Results The FMC level decreased in the order of shortened, within, and prolonged groups, and the decrease was statistically significant among all three group pairs. The opposite tendency was observed for Fbg and fibrinolysis-related markers of α2-PI and Plg, and significant differences were recognized in all pair comparisons except for between within and prolonged groups in Plg. The mean values of the fibrinolysis markers D-dimer and PIC in all three groups were higher than the cut-off values, and the PIC value differed significantly between the within and prolonged groups.Conclusion The fibrinolysis reaction was detected in all three groups, but the status differed. CFWA has the potential to reflect the fibrinolysis status in one global assay.
Keywords: clot-fibrinolysis waveform analysis; coagulation and fibrinolysis; fibrin; tissue-type plasminogen activator; fibrinolysis